CREATING CARING COMMUNITIES: SOCIAL CAPITAL FORMATION AND AGING IN PLACE - Scharlach, A.E. (Innov Aging, 2017)
Communities throughout the world are seeing the emergence of new types of consumer-driven support structures to promote aging in place, driven in part by global transformations in traditional family and societal supports. Of particular interest are grassroots community-based efforts that not only provide needed assistance, but also promote social connection, meaningful activity, civic engagement, and an increased sense of communal trust and solidarity. This symposium examines existing evidence regarding four of these initiatives: the Village model (US, Netherlands, Australia), Supportive Communities (Israel), Active Caring Communities (Belgium), and civil society voluntary care networks (Sweden). In the Village model, older community members create their own elder-led support organizations, assuming primary responsibility for operations, financing, and peer support. In Supportive Communities, a retired community member serves as a convener and key source of social and instrumental support, with administrative and financial assistance from the government. Active Caring Communities involve a neighborhood-organized model of care that supports frail older people to age in place in deteriorated neighborhoods. Finally, Swedish data examine the growth of peer and cross-generational informal assistance networks in the context of declining societal supports for older adults. Leading scholars will critically examine existing knowledge regarding each of these approaches, with particular attention to the ways in which they contribute to individual well-being, community social capital, and the ability to age in place.